Venture waqf in a circular economy - Tariqullah Khan (ISRA International Journal of Islamic Finance, 2019)
Purpose: This paper aims to enhance the impact of incorporated waqf institutions by blending their resources to promote responsible small businesses that are inclusive of human development, service to society and preservation of ecological environment and other species. This is expected to shift the paradigm of businesses from the current waste-oriented linear economy to ideally a zero-waste circular economy. Design/methodology/approach This is an analytical study building on the experience of European Venture Philanthropy Organizations (VPOs) that work with the primary objective of making impactful businesses successful, with capital protection and return on investment being of secondary concern. This paper suggests an incorporated institutional design that blends resources for promoting responsible businesses using a new hybrid financial mechanism, namely, equity-at-default (EaD) to replace collateral and foreclosure requirements with responsibility and compassion. Findings The research calls for changing the business paradigm from linear to circular, an incorporated institutional framework for venture waqf, Purpose: of the waqf to make impactful small businesses successful and designing a financial contract to loan in favor of responsible businesses that convert to equity stake for the waqf in case of default (EaD) replacing collateral and foreclosure requirements. Research limitations/implications This is a theoretical study motivated by the success of VPOs but assigns a new role to waqf institutions. Furthermore, the incorporated nature of waqf is a new idea and EaD is a new mechanism. Being new, these ideas have the risk of not being implemented. However, the broader message that waqf shall promote businesses that are inclusive of ecological concerns is generally applicable. Practical implications The paper has a significant practical implication to transform the responsibility and consciousness of businesses. Waqf is fundamentally a compassionate institution, and it must enhance the responsibility of businesses to become more inclusive of the environment and other species. It should also become more compassionate toward businesses that are in distress and default. In this sense, the paper tries to internalize compassion in financial contracting that can potentially change the architecture of lending. Social implications Altering businesses' mindset from a waste-driven extractive linear economy to inclusive circular economy has a tremendous transformative role. This will have implications for enhancing business consciousness and responsibility. As poverty is a phenomenon of state of mind, changing the society's state of thought in Muslim communities is expected to have basic positive implications. Entrepreneurs with a new mindset can have far-reaching positive impacts on the society. Originality/value The paper offers potentially innovative perspectives in four key areas and blends the different resources in an incorporated waqf that makes responsible entrepreneurs assume a partnership role in times of distress through EaD. Furthermore, the integration of compassion in financial contracting could have better implications for return on investment as well. The ideal state of an economy is where waste is turned into wealth and well-being is something that all policymakers must keep on the top of their agendas.
Keywords: 330; Waqf; Circular economy; Venture philanthropy; Zero-waste economy; Equity-at-default